ABC portal: a single-cell database and web server for blood cells. Issue Volume 51:Issue D1(2023) (3rd August 2022) - Gao, Xin; Hong, Fang; Hu, Zhenyu; Zhang, Zilong; Lei, Yang; Li, Xiaoyun; Cheng, Tao
Abstract: ABC portal (http://abc.sklehabc.com ) is a database and web portal containing 198 single-cell transcriptomic datasets of development, differentiation and disorder of blood/immune cells. All the datasets were re-annotated with a manually curated and unified single-cell reference, especially for the haematopoietic stem and progenitor cells. ABC portal provides web-based interactive analysis modules, especially a comprehensive cell-cell communication analysis and disease-related gene signature analysis. Importantly, ABC portal allows customized sample selection based on a combination of several metadata for downstream analysis and comparison analysis across datasets. ABC portal also allows users to select multiple cell types for analysis in the modules. Together, ABC portal provides an interactive interface of single-cell data exploration and re-analysis with customized analysis modules for the researchers and clinicians, and will facilitate understanding of haematopoiesis and blood/immune disorders.